Legal status of members of limited partnerships - Butryn-Boka Nataliіa; Duban, Ivanna (Actual problems of law (Aktual’ni problemi pravoznavstva), 2024)
A business partnership that combines the features of a limited liability partnership and a general partnership is a so-called limited partnership. Of course, a partnership is recognized as a limited partnership in which, together with one or more participants who carry out business activities on behalf of the partnership and bear responsibility for the obligations of the partnership with all their property, there is one or more participants whose liability is limited to the contribution to the property of the partnership (contributors), and participants can be citizens and legal entities (enterprises). An important point is that if two or more members participate in a limited partnership with full responsibility, they are jointly and severally liable for the debts of the partnership. This organizational and legal form in today’s conditions, unfortunately, has fallen from the popularity ratings. However, it is worth noting that the relevance of the study of issues related to the activities of limited partnerships is not lost, since the recovery of the economy will require various forms of management, and for this we will determine certain features: in the founding agreement, only the aggregate size of their shares in the company’s property is indicated in relation to investors, as well as the size, the composition and order of their contributions. As in other partnerships, the depositor’s entry into the limited partnership is carried out through making contributions, but the legislation specifies that these should be monetary or material contributions. It is important that intangible values​and rights of use cannot be contributions of members of the limited partnership.Note that, accordingly, the obligations of limited partnership investors have special features. According to the regulatory framework, the investors of the limited partnership must make contributions and additional contributions in the amount, in the ways and in the order provided by the founding agreement. The specifics of managing a limited partnership, first of all, is that it is carried out only by participants with full responsibility. If there is only one member with full responsibility in the limited partnership, the management of affairs is carried out by this member independently. Depositors do not have the right to interfere with the actions of participants with full responsibility for managing the limited partnership’s affairs. Since they risk within the limits of their contributions and only theirs, they have practically no right to manage, but only the right to receive income. At the same time, investors have the opportunity to participate in management. A characteristic feature of limited partnerships is that the depositor of the limited partnership is responsible for the debts of the partnership, which arose before he joined the partnership, to third parties in the same manner as other contributors. As we can see, the rather complex structure of organizational and economic relations, the imperfection of national legislation have led to the fact that today limited partnerships in our country are not very popular, even taking into account the fact that this form of management is quite convenient in the practical sphere of doing business.